Supernumerary chromosome variants in Dichroplus elongatus (Acrididae): Fluorescent banding and cline variation pattern - Rosetti, Maria Eva Natalia (2010)
Dichroplus elongatus is a South American grasshopper that shows simultaneous polymorphisms for B chromosomes and several supernumerary segments located in chromosome pairs S10, S9, and M6 (SS10, SS9 and SS6 respectively), in natural populations from Argentina. Heterochromatin characterization with DAPI-CMA3 banding reveals that B chromosomes show an interstitial GC-rich band. The distal SS10 segment seems to also be GC-rich, whereas the proximal supernumerary segments (SS6 and SS9) show two different heterochromatin regions: one GC-rich region (CMA3 /DAPI-) and the other that has no specificity to AT or CG base pairs (CMA3/DAPI dull). The results obtained permit us to distinguish two types of constitutive heterochromatin in the supernumerary segments of D. elongatus. The variation in the frequency of these chromosome polymorphisms was analysed with respect to some climatic and geographic variables. There is considerable B chromosome variation between populations, and this variation correlates negatively with latitude and positively with altitude and mean annual temperature. The incidence of the proximal SS9 segment is positively correlated with altitude. The pattern of chromosome variation is discussed in relation to the population's ability to maintain supernumerary DNA in more climatically favorable geographic regions.